Development Of A Creative Economy Based On Cultural Capital In The Culinary Sector Of West Sumatra Tourism Destinations - Zusmelia, Zusmelia; Ansofino, Ansofino; Irwan, Irwan; Ronald, Jimi; Cahyani Lubis, Gebi (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The focus of this study is to analyze the development of a creative economy based on cultural capital in the culinary field in the tourist destinations of West Sumatra.This study uses a qualitative approach that takes a descriptive type. Purposive sampling was used to select research informants. Research informants are creative economic actors in the culinary sub-sector. The data collection method begins through indepth interviews, observations and document data collection. The unit of analysis is carried out from several stages, one of which is data collection, data reduction, data analysis and drawing conclusions which are referred to in the Miles and Huberman model. The results of this study indicate that in the development of the creative economy, the culinary sub-sector based on cultural capital has reached a stage that generates added value. The development of a creative economy based on cultural capital is part of how creative entrepreneurs in the culinary field gain networks with shared knowledge, skills and most importantly a high sense of culture, so that they can create many benefits for fellow citizens. In developing this creative economy, the culinary sub-sector can not only create a unique or distinctive taste, but has reached the stage of creating job opportunities for the local community, adding insight and knowledge and raising social status in society. Coupled with the culinary uniqueness provided by each creative artist, it adds value to the marketability and memory of visitors to visit again.